Life cycle assessment of broiler chicken production: a portuguese case study - González-García, Sara
An environmental assessment of the life cycle of broiler chicken production from a cradle-to-slaughterhouse gate perspective was carried out with the aim of identifying the environmental hotspots of the system. To do so, broiler chicken production in Portugal was investigated in detail. Inventory data for the different production stages (chicken farm- and slaughterhouse-related activities) was gathered in collaboration with an integrated Portuguese chicken company. Results showed that the chicken farm is the main factor responsible for the environmental impacts analysed. Specifically, both feed production and on-farm emissions were the main environmental hotspots. Concerning the slaughterhouse-related activities, the production of electricity and packaging materials presented a significant contribution at this stage. The environmental results were compared with other published Life Cycle Assessment studies of chicken production in other countries, with special attention paid to the quantification of greenhouse gas emissions. A number of improvement actions are proposed to reduce the environmental impacts of poultry litter management and feed production. Moreover, studies of pork, beef and fish (sardines) were also included for comparison using a functional unit based on an identical protein content. The results (excluding subsequent packaging) showed that the production of broiler chicken could be preferable in comparison to other types of meat due to its lower global warming potential. On the contrary, sardines presented a reduction of 88% in comparison with the chicken profile; however, the availability of sardines for consumption may be limited throughout the year due to EU fishing protocols concerning sea stocks protection.